THE UGBO-MAHIN CONFLICT AND ITS IMPLICATIONS FOR SOCIAL DEVELOPMENT IN ILAJE SOCIETY (2012)
Available literature on Ilaje society has been concerned with the legal framework of colonial rule, indigenous political structure, economic development and missionary activities. There has not been any extensive study on the Ugbo-Mahin conflict and its implications for social development. This study, therefore, examined the Ugbo-Mahin conflict in Ilaje area of Ondo state with specific focus on its implications for social relations, oil exploration and compensation, infrastructural development, kingship and religious institutions. The study also investigated and interrogated the pre-conflict pattern of interactions between the Ugbo and the Mahin and how they have been affected. The principal instrument of data collection for the study was the unstructured interview. In-depth interview were held with fifty community and opinion leaders from each of the two communities. Four Focus Group Discussions were held with persons knowledgeable about the conflict. Archival materials, petition and letters of protest and photographs were used. Data were also collected from reports of government commissions of inquiry, books, journals, newspapers and internet materials. The data were then subjected to content analysis. The Ugbo and Mahin had friendly relationship before the advent of colonial rule. The Ugbo-Mahin conflict dated back to the colonial period and is carried into contemporary times. The conflict has led to destruction of lives and property in the area. Different ethnic unions of parallel functions have emerged in the two communities. These unions have used their rivalry to stall industrial development by demanding separately for improved social life. The Ugbo-Mahin incessant conflicts have, thus, undermined development in the two communities such that there are no industrial estates, manufacturing companies and large business investment. The conflict has further put stress on marital harmony between the two groups. However, the conflict has not escalated into unmanageable situation because of the activities of the Ilaje Youth Forum, the National Association of Ilaje Students and Egbe OmoIlaje who are responsible for peace building and reconciliation of all aggrieved parties in both communities. In spite of the efforts of these associations, the marginalization of the Mahin in the compensation on oil spillage and other ecological problems occasioned by the oil exploration in Ugboland and the discrimination against them in appointment of representatives to oil commissions are some of the factors inhibiting sustainable peace and development. The Ugbo-Mahin conflict over the years had done incalculable damage and has not allowed harmonious relationship between two ethnic groups. There is a need for the promotion of non-violent means in managing the conflict and facilitation of peace education in the society. Both of which aim at psycho-social healing and psychological transformation towards peaceful co-existence in the two communities. There is need for the encouragement of inter-marriages and cultural re-integration of the two groups.